Interlocking corporate and policy networks in financial services: Paris-London relations post Brexit - Sarah Hall; Martin Heneghan (ZFW - Advances in Economic Geography, 2023)
This paper examines the impacts of Brexit as an external shock to European financial centre relations. In particular, it studies the changing nature of Paris-London financial relations post Brexit. Early on in the Brexit process, Paris was not understood as the most likely European centre to benefit from Brexit given its tax regime and high office costs. However, our analysis shows that through policy and corporate network change, it has been one of the major beneficiaries. In making this argument, the paper develops a sympathetic critique of work on global cities that has tended to emphasise corporate networks without fully situating them within their political landscapes. We argue that bringing work in economic geography into closer dialogue with work in international political economy offers one fruitful way of addressing this oversight and, in turn, better understanding how inter-city relations respond to external shocks.
Keywords: 330; Brexit; financial services; international financial centres; London; Paris